The Strategy for Ecotourism Development in Plantation Area: A Case Study from Kalibendo Plantation, Banyuwangi East Java - Linda Herawati; Muhammad Izzuddin Faizal; Paisal Ansiska; Rona Aji Lestyaningrum; Zulfaidha Zulia (Journal of Indonesian Tourism and Development Studies, 2016)
Kalibendo plantation have a high potential value to be developed as an ecotourism destination. As far, the development of tourism in the area is still lack of visitors’s enthusiasm due to several reasons such as lack of tourism product, promotion, poor management, and the low involvement of local people in tourism development. The aims of this study are to determine the visitor’s perceptions at Kalibendo plantation tourism objects and arrange the strategy to develop ecotourism in that area. The results of visitors’ assessment about tourism on Kalibendo plantation was moderates. Many programs should be developed systematically. The indicators of visitors’ satisfactions are ‘Sapta Pesona’ that consists of security, order, cleanliness, coolness, beauty, friendliness, and memories should be improved. The strategy of tourism development in the Kalibendo plantation tourism objects which is based on SWOT analysis are: 1) The co-operation between local government with tourism management, namely PT. Kalibendo shuld be improved; 2) Organizing the education concerning to the prevention of environmental damage should be formulated; 3) The improvement of local human resources around the tourism objects through training should be implemented; and 4) The improvement of facilities for tourists should be planned and developed following ecotourism principles.Keywords: Ecotourism, Banyuwangi Regency, plantation, tourism attraction development.